Expanding the phenotypic spectrum of non-alcoholic fatty liver disease and hypertriglyceridemia - Meroni, Marica; Longo, Miriam; Paolini, Erika; Tria, Giada; Ripolone, Michela; Napoli, Laura; Moggio, Maurizio; Fracanzani, Anna Ludovica; Dongiovanni, Paola (Frontiers in Nutrition, 2022)
Background & Aims: Hypertriglyceridemia is a common feature of Metabolic Syndrome (MetS) as well as of nonalcoholic fatty liver disease (NAFLD), which is considered the hepatic manifestation of MetS. Fat accumulation in hepatocytes may alter mitochondrial homeostasis predisposing to advanced liver disease. Here, we report a case of a 40-year-old woman with early aggressive NAFLD due to severe hypertriglyceridemia ensued from a combination of genetic variants and additional metabolic risk factors. Methods: Genetic screening was performed by using whole-exome sequencing and mitochondrial structures were evaluated by Transmission Electron microscopy (TEM). Results: At presentation, the patient is reported to have hepatomegaly, hypertriglyceridemia and raised transaminases. Genetic analysis revealed that the patient beard heritable alterations in genes implicated in lipid handling, among which APOB, APOE, CETP and HSPG2, accompanied by missense mutations in genes involved in mitochondrial function, i.e., AK2, ALG6, ASPA, NDUFAF1, POLG, TMEM70. Abdominal ultrasound (US) and transient elastography were suggestive of severe hepatic steatosis and fibrosis. Liver biopsy confirmed the diagnosis of nonalcoholic steatohepatitis (NASH)-related fibrosis. Thus, to better outline whether mutations involved in lipid remodeling and mitochondrial function may affect also organelles’ morphology, we exploited TEM. Along with multifaceted abnormalities of mitochondrial architecture that have been already observed in NAFLD patients, astonishing ultrastructural defects, such as mitochondrial vacuolization, sub-compartmentalization and onion-like mitochondria were identified. Conclusions: The anomalies reported may expand the phenotypic spectrum of mitochondrial abnormalities observed in NAFLD patients, which may possibly contribute to the switching towards progressive NAFLD.